The Effect of The Mnemonic Keyword Method of Foreign Language Vocabulary Learning: Cognition and Metacognition Perspective - Irsyad, Muhamad Faqih (Cognicia, 2019)
The Keyword Method (KWM) is a mnemonic method designed to assist learners in learning foreign vocabulary. The method encompasses two processes, namely, the similarity of the words in sound(s) or the similarity of the keyword spoken with foreign language words and created mental images. This case study of the intervention involved a 26 years old student who had newly commenced as a first-year Indonesian studies student at Flinders University, Adelaide. She is a locally born Australian student who speaks English as her native language. To interpret the result findings, the checklist method (consisting of correct, doubt, and no responses), descriptive analysis, and interviews, as well as observations, have been applied in the KWM implementation. The results proved that the KWM has successfully assisted the learner in improving her Bahasa Indonesia, both in acquisition and retention, in a more effective manner compared to her other study strategies. This was especially apparent after conducting the immediate and delayed comprehensive test. The subject was also able to generate self-regulated learning. This indicated that the subject is able to metacognitively, motivationally and behaviorally utilize her cognitive sources to control the tasks. Cognitive and metacognitive processes of the KWM implementation, involving the detailed information processing of the learner, are discussed here.